2011
DOI: 10.5194/hess-15-2291-2011
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying flow and remediation zone uncertainties for partially opened wells in heterogeneous aquifers

Abstract: Abstract. This study presents a numerical first-order spectral model to quantify transient flow and remediation zone uncertainties for partially opened wells in heterogeneous aquifers. Taking advantages of spectral theories in solving unmodeled small-scale variability in hydraulic conductivity (K), the presented nonstationary spectral method (NSM) can efficiently estimate flow uncertainties, including hydraulic heads and Darcy velocities in r-and z-directions in a cylindrical coordinate system. The velocity un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Away from the inlet and outlet boundaries, we found that the velocity variance along the x direction showed a relatively stationary zone. This behavior had been observed in groundwater flow in porous media (Ni et al, 2010(Ni et al, , 2011. The distance of the variance transition zone was close to 0.5 m from the boundaries.…”
Section: Sampling Volumes and Flow And Transport Uncertaintiessupporting
confidence: 72%
See 1 more Smart Citation
“…Away from the inlet and outlet boundaries, we found that the velocity variance along the x direction showed a relatively stationary zone. This behavior had been observed in groundwater flow in porous media (Ni et al, 2010(Ni et al, , 2011. The distance of the variance transition zone was close to 0.5 m from the boundaries.…”
Section: Sampling Volumes and Flow And Transport Uncertaintiessupporting
confidence: 72%
“…Specifically, the DFN transport was mainly modeled based on Lagrangian approaches such as particle tracking and random walk algorithms (e.g., Makedonska et al, 2015;Painter et al, 2008;Stalgorova and Babadagli, 2015;Wang and Cardenas, 2015). Numerical solutions to the ADE based on the Eulerian approach have not been widely implemented because of computational issues, such as numerical dispersion and convergence in the model for complex fracture connections (Odling, 1997;Berrone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that the velocity variance along the x-direction showed a relatively stationary zone away from the inlet and outlet boundaries. This behavior had been observed in groundwater flow in porous media (Ni et al, 2010(Ni et al, , 2011. The distance of the variance transition zone was close to 0.5 m from the boundaries.…”
Section: Sampling Volumes and Flow And Transport Uncertaintiesmentioning
confidence: 70%